Medical student preferences for the internal medicine residency interview day: A cross-sectional study. - Amar R Chadaga; Dana Villines; Armand Krikorian (PLoS ONE)
Background Applicant recruitment is an essential part of a residency program's activities with valuable resources dedicated to ensuring its success. Most programs design interview days based on a mix of tradition, budget availability and perception of applicant preferences. There is a paucity of available data on preferences of applicants for interview days. Objective We sought to investigate Internal Medicine applicant preferences for a residency recruitment day in aggregate and stratified by medical school background: United States vs. International Medical School Graduate. Methods A survey was developed and used in a cross-sectional study of Internal Medicine categorical and preliminary medicine candidates. Applicants ranked different facets of the interview day using a Likert scale. Variables included interview type, start time, length of interview day, number of interviews, length of each interview, background of interviewers, types of questions, interaction time with residents, month of interview, and components of interview day. Results 265 applicants received the surveys and 215 completed them correctly (81%). Overall, applicants tended to favor an 8-9 am start time (81.9%) and an optimal duration of four hours (82.8%). The interview was the most preferred component of the day (80.0%) with one-on-one (98.1%) and 15-30 min (95.3%) interviews preferred. Several statistically significant differences were found between the United States and International students as well as Categorical and Preliminary applicants. Conclusion Our findings offer insights into various factors of the interview day that may appeal to Internal Medicine candidates. This information will be useful to graduate medical education departments engaged in recruitment.